La moneda de los príncipes herederos en los reinos de la Europa Occidental en la Baja Edad Media (s. XVI-XV) - Francisco Olmos, José María de (Documenta & Instrumenta - Documenta et Instrumenta, 2008)
This items studies the institutional enhancement that the heir of the Crown wins in France and England from the middle of the XIVth century, which included the right to coin. The many cases brought as examples are as different as the political situation where they took place: while that of the Black Prince was an exception, that of the Dauphin enjoied a certain continuity. Charles of Viana was a perfect example of the struggle for power and vindication of rights, and this example was followed by Isabel of Castile.